Effect of Monoculture and Polyculture Systems on Growth and Production of Fishes in Seasonal Waterbodies of Haor Villages, Sunamganj District - Ali, M. S.; Islam, M. S.; Begum, N.; Suravi, I. N.; Mia, M.; Kashem, M. A. (Journal of Scientific Research, 2017)
The study was conducted to assess the growth and production of Thai sarpunti (Puntius gonionotus), tilapia (Oreochromis niloticus) and rui (Labeo rohita) under monoculture and polyculture systems in seasonal waterbodies of haor environment. Selected waterbodies were divided into three treatments as T1 (sarpunti), T2 (sarpunti+tilapia) and T3 (sarpunti+tilapia+rui). Each treatment had three replicates and same stocking density (40,000 ha-1) of fishes was maintained in all treatments. Stocked fishes were fed with rice bran and wheat flour as supplemental feed at a decreasing rate of 10-5% of total biomass for twice daily. The highest final weight of sarpunti (122.32 g), tilapia (102.58 g) and rui (140.0 g) was obtained in T1, T2 and T3, respectively. Significantly higher production of sarpunti was secured in T1 (3,446.13 kg ha-1) than T2 (2,942.6 kg ha-1) and T3 (2,804.1 kg ha-1), and tilapia production was better in T2 (2,786.07 kg ha-1) than T3 (2,172.52 kg ha-1). Combined production of sarpunti, tilapia and rui was significantly (p<0.05) higher in T3 (8,341.41 kg ha-1) followed by T2 (5,728.67 kg ha-1) and T1 (3,446.13 kg ha-1). Therefore, polyculture practice of sarpunti, tilapia and rui may be suggested to disseminate at farmers level for boost up fish production.